NILAI-NILAI PEMBINAAN AKHLAK DALAM KEGIATAN EKSTRAKURIKULER DI MADRASAH ALIYAH MUSTAFAWIYAH PURBA BARU KABUPATEN MANDAILING NATAL - Herman Pelangi (Universitas Muhammadiyah Tapanuli Selatan, 2017)
Islam puts moral in an important place and has a vital function in guiding the social life in a country. Madrasah Aliyah Mustafawiyah Purba Baru Kabupaten Mandailing Natal has a strong commitment and the seriousness in founding the extracurricular education, so that it will produce the high achievement, the interesting point of extracurricular education is it can give positive impact to the student’s moral. The formulations of the problem in this research were the extracurricular activities, the founding of moral value, and the endorser and inhibitor factor of extracurricular in founding the student’s moral in Madrasah Aliyah Mustafawiyah Purba Baru Kabupaten Mandailing Natal. Moreover, the method of this research was descriptive qualitatif which choose the leader of Pondok Pesantren, headmaster, teacher and student of Madrasah Aliyah as the respondent of the research. The technique of collecting data used in this research was observation, interview and documentation and it analysed throuh reducing, displaying and verifiying the data to get the conclusion qualitatively. As the result of this research were mention in the following, first, there are five types of extracurricular education in founding the student in Madrasah Aliyah Mustafawiyah Purba baru Kabupaten Mandailing Natal, which are religion and sport program, art and skill activity, student’s organisation, and educative tour; second, education extracurricular process in Madrasah Aliyah Mustafawiyah Purba Baru Kabupaten Mandailing Natal is running well, it seems the activity has programmed well, time and place is schedule regularly and selective, the method use is variative and orientiate to the the doundation of the student’s moral, and the regularly evaluation; third, extracurricular education gives posititive impact to the student’s moral, not only in relation to Allah SWT but also, to teacher, parents, friends and themself; fourth, the inhibitor factors are: the lack offacility, unprofessional teacher with low religion skill, and the low quality of students and; fifth, the solution is the cooperation of the foundation, workshop, reschedule effectively, have an experienced trainner, giving advices and giving the punishment to students.